Compensation of transmission channel effects in chaos synchronization - Buscarino, A.; Fortuna, L.; Frasca, M.; Sciuto, G.; Rashid, M. T. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
The synchronization of chaos is a well-known topic which attracted the attention of the scientific community in the last two decades. However, the robustness of the synchronous state has been not widely studied, especially considering real cases in which the effects introduced by the physical channel through which chaotic circuits interact, may deeply influence the quality of synchronization and even the onset of it. In this paper, the synchronization of two chaotic circuit coupled through a non– ideal channel is investigated. In particular, the effects of channels introducing a frequency–independent or frequency–dependent time–delay are investigated. Furthermore, two different design strategies to obtain a linear compensation block able to compen- sate the considered channel effects are presented and the recovery of the synchronous state is discussed.